The influence of in-season training loads on injury risk in professional rugby union - Cross, M. J.; Williams, S.; Trewartha, G.; Kemp, S. P. T.; Stokes, K. A. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To explore the association between in-season training-load (TL) measures and injury risk in professional rugby union players.